Peningkatan Kemampuan Pemahaman Matematis Siswa Menggunakan Pembelajaran Matematika GASING (Gampang, ASyIk, dan menyenaNGkan) - Armianti Armianti; Dawuh Nuril Wildan; Robiansyah Robiansyah; Oktarika Trissiana; Rully Charitas Indra Prahmana (Universitas Hamzanwadi, 2016)
This research is motivated by the low student learning outcomes in the material triangle and parallelogram caused by a lack of understanding of students about the forms of flat wake triangle and parallelogram so when the teacher gives about the shape Flat figure that is different from that taught teachers, students find it difficult to do. Therefore the use of learning with math GASING (easy, fun, and enjoyable). The purpose of research is to know the size of the average N-gain in the ability of students mathematical understanding once taught using learning math GASING. This research was conducted in SDN RUMPAKSINANG with grade IV samples of 31 people in November 2015. The method used in this research is the type pre-experimental design with the design of one group pretest-posttest. The results showed from this research that there is an increased ability to learn the students' understanding after learning of Mathematics GASING. The increase was seen from the average N-gain of 0.3813 which is included in the medium category.